Women and Work in the Dutch Republic - Schmidt, Ariadne (Early Modern Low Countries, 2025)
Historiography on women and work focused for long on whether and how large-scale transformations – such as urbanisation, commercialisation, the rise of capitalism, the consumer revolution, industrialisation, and the ideal of domesticity – changed women’s socio-economic position and work opportunities. More recent research also turns the question around and looks at the impact of women’s socio-economic position and gender relations on economic change. This essay discusses what these approaches have contributed to our knowledge and understanding of women and work in the Low Countries (with a specific focus on the Dutch Republic), identifies gaps in historiography, and argues that further diversification is necessary in order to better understand women’s economic contribution and the impact of gender relations on economic development.